Preparation method and application of CuGaS2at-TiO2 composite material photocatalyst

By growing CuGaS2 quantum dots in situ on the surface of TiO2 hollow spheres, forming a CuGaS2@TiO2 composite photocatalyst with direct Z-shaped heterostructure, the problem of insufficient degradation ability of existing CuGaS2 quantum dots on methyl orange is solved, and efficient Methyl orange degradation and stable catalytic properties.

CN119114105APending Publication Date: 2024-12-13ORDOS INST OF APPLIED TECH +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411028189.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing CuGaS2 quantum dot photocatalyst has limited ability to degrade methyl orange pollutants, which limits its application in environmental purification.

Method used

The CuGaS2 quantum dots are loaded on the surface of TiO2 hollow spheres by in-situ growth method to form a CuGaS2@TiO2 composite photocatalyst with a direct Z-type heterostructure, which improves the recombination efficiency of electrons and holes.

Benefits of technology

Under ultraviolet light, the degradation rate of CuGaS2@TiO2 composite photocatalyst on methyl orange reached 95.72%, and the degradation rate remained above 94% in four cycle experiments, significantly improving catalytic activity and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2SXZKLDFQZXBSH7Q9FWPQETHD8FTJUTJRI60FPGO
    Figure 2SXZKLDFQZXBSH7Q9FWPQETHD8FTJUTJRI60FPGO
  • Figure U4LARLV3XUEL4E8JX2OL8YEOUCRJGWR1QTRTTBK7
    Figure U4LARLV3XUEL4E8JX2OL8YEOUCRJGWR1QTRTTBK7
  • Figure UPKRW9PD0ZROBF90CFSSITEHUTFIKN6VZ2BIPEYL
    Figure UPKRW9PD0ZROBF90CFSSITEHUTFIKN6VZ2BIPEYL
Patent Text Reader

Abstract

The invention discloses a preparation method of a CuGaS2-coated TiO2 composite material photocatalyst, which comprises the following steps: mixing a copper source, a gallium source, octadecene and oleylamine, adding TiO2 hollow spheres, and uniformly mixing under protective gas; adding a sulfur precursor solution, heating to 180-260 DEG C, and reacting for 25-30 minutes; and quenching and purifying. The CuGaS2 quantum dots are successfully loaded on the surfaces of the TiO2 hollow spheres through an in-situ growth method, the CuGaS2 / TiO2 composite material photocatalyst with a direct Z-type heterostructure is formed, and the compounding efficiency of electrons and holes is greatly reduced. The CuGaS2-coated TiO2 composite material photocatalyst prepared by the invention has higher catalytic activity, the degradation rate of methyl orange under ultraviolet irradiation for 30 minutes can reach 95.72%, the degradation rate is still 94% or more after four cycle experiments, and the CuGaS2-coated TiO2 composite material photocatalyst has excellent stability, can be repeatedly used for multiple times, and has great application potential in the aspect of water pollution treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalysts, and specifically relates to a preparation method and application of a CuGaS2@TiO2 composite material photocatalyst. Background Art

[0002] Methyl orange is a common pollutant in dye manufacturing and other industries. Due to improper wastewater discharge, when it enters water bodies and soil through the water circulation system, a large amount of residue will be produced, which brings troubles to human survival and causes certain pollution to the environment. Methyl orange is an aromatic compound containing azo double bonds. Its complex chemical structure makes it highly stable and difficult to degrade through natural processes. In addition, residual methyl orange easily accumulates in water bodies, causing environmental pollution problems, causing serious visual pollution and biological toxicity. Commonly used methods for treating methyl orange pollutants include physical methods, biological methods, chemical methods, etc. These methods each have their own advantages and limitations. Compared with the above methods, photocatalysis, as an environmentally friendly green technology, has become a research hotspot in wastewater treatment.

[0003] Since Fujishima and Honda reported in the 1970s that TiO2 and platinum electrodes were used to form a photoelectrochemical system to decompose water into hydrogen and oxygen, the photocatalytic activity of TiO2 has attracted widespread attention. As an n-type semiconductor material, TiO2 has great application value in photocatalytic environmental purification and solar energy conversion due to its advantages such as high refractive index, wide band gap, stable chemical properties, strong resistance to photocorrosion, and low price. Among them, anatase phase TiO2 has a wide energy band gap, can degrade various pollutants in air and water, and shows high photocatalytic activity. In order to further improve its photocatalytic activity, a composite structure is usually designed to improve the charge separation efficiency and improve light absorption by doping and surface modification. Since CuGaS2 material is green, non-toxic, highly stable, and has an optical band gap of about 2.4eV, which is similar to the optical band gap of Cd and Pb sulfides, it is an ideal alternative material for Cd and Pb sulfide quantum dots, especially in terms of environmental and health safety. However, the degradation ability of CuGaS2 quantum dot photocatalysts prepared by existing technologies for methyl orange pollutants is limited, which limits its application. Summary of the invention

[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a method for preparing a CuGaS2@TiO2 composite material photocatalyst to improve the degradation ability of CuGaS2 quantum dots on methyl orange pollutants.

[0005] To achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a CuGaS2@TiO2 composite material photocatalyst, comprising the following steps: After mixing copper source, gallium source, octadecene and oleylamine, add TiO2 hollow spheres and mix evenly under protective gas; add sulfur precursor solution, heat to 180-260℃, react for 25-30min; quench and purify; Among them, the dosage ratio of the copper source, gallium source, octadecene, oleylamine, sulfur precursor solution and TiO2 hollow spheres is 0.1mmol:0.1mmol:10mL:3mL:1mL:0.7~4.7mmol, the sulfur precursor solution is an oleylamine solution of sulfur powder, and the dosage ratio of sulfur powder to oleylamine is 1mmol:1mL.

[0006] Preferably, the preparation method of the TiO2 hollow spheres is: adding titanium tetrachloride and acetone to anhydrous ethanol, hydrothermally reacting at 220°C in a high-pressure reactor for 12 hours, washing the product to neutrality after cooling, drying, and calcining at 650°C for 150 minutes to obtain the product.

[0007] Preferably, the usage ratio of titanium tetrachloride, acetone and anhydrous ethanol is 1 mL:24 mL:96 mL.

[0008] Preferably, the copper source is cuprous chloride, and the gallium source is gallium chloride.

[0009] Preferably, the quenching method is to rapidly cool in a 25°C cold water bath.

[0010] Preferably, the purification method is to wash the precipitate with anhydrous ethanol after centrifugation to obtain the CuGaS2@TiO2 composite material photocatalyst.

[0011] The present invention also provides a CuGaS2@TiO2 composite material photocatalyst prepared by the preparation method.

[0012] Preferably, the CuGaS2@TiO2 composite material photocatalyst is a TiO2 hollow sphere surface loaded with CuGaS2 quantum dots to form a direct Z-type heterostructure, wherein the mass fraction of the CuGaS2 quantum dots is 5-25%.

[0013] The present invention also provides the use of the CuGaS2@TiO2 composite material photocatalyst in degrading organic pollutants.

[0014] Preferably, the organic pollutant is methyl orange.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention successfully loads CuGaS2 quantum dots on the surface of TiO2 hollow spheres through an in-situ growth method, forming a CuGaS2@TiO2 composite material photocatalyst with a direct Z-type heterostructure, which greatly reduces the recombination efficiency of electrons and holes. The CuGaS2@TiO2 composite material photocatalyst prepared by the present invention has higher catalytic activity, and the degradation rate of methyl orange can reach 95.72% under ultraviolet light in 30 minutes, and the degradation rate is still above 94% after four cycle experiments. It has excellent stability and can be reused many times, and has great application potential in water pollution treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 XRD pattern of the CuGaS2@TiO2 composite material photocatalyst prepared in Example 1; Figure 2 TEM image of the CuGaS2@TiO2 composite material photocatalyst prepared in Example 1; Figure 3 This is the XPS graph of the CuGaS2@TiO2 composite material photocatalyst prepared in Example 1; Figure 4 These are the test results of the degradation ability of the CuGaS2@TiO2 composite material photocatalyst prepared in Example 1 on MO. DETAILED DESCRIPTION

[0017] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can more clearly understand the present invention. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. In the embodiments of the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art; unless otherwise specified, the technical means used are conventional means well known to those skilled in the art.

[0018] Example 1 Preparation of CuGaS2@TiO2 (CGS / TiO2) composite photocatalyst The preparation method of the CuGaS2@TiO2 composite material photocatalyst provided in this embodiment comprises the following steps: (1) Add 0.25 mL of titanium tetrachloride and 6 mL of acetone to 24 mL of anhydrous ethanol, stir thoroughly until a colorless and transparent solution is formed, transfer to a high-pressure reactor, perform a hydrothermal reaction at 220 °C for 12 h, and then cool naturally. Wash the product with deionized water until it is neutral, dry it, and calcine it at 650 °C for 150 min to obtain TiO2 hollow spheres. (2) Add 15 mL of oleylamine and 0.48 g of sulfur powder into a three-necked flask, perform triple degassing to remove moisture and other gas impurities, heat to 90 ° C under nitrogen protection and maintain for 5 minutes, and cool naturally to obtain a sulfur precursor solution; (3) In a three-necked flask, 9.9 mg of cuprous chloride, 17.62 mg of gallium chloride, 10 mL of octadecene, and 3 mL of oleylamine were mixed, and TiO2 hollow spheres were added. The mixture was mixed evenly under nitrogen protection, and 1 mL of sulfur precursor solution was added. The mixture was heated to 220 °C and reacted for 25 min. After the reaction, the three-necked flask was quickly cooled in a 25 °C cold water bath, and the precipitate was washed with anhydrous ethanol after centrifugation to obtain a CuGaS2@TiO2 composite material photocatalyst.

[0019] In this embodiment, 5 groups of CuGaS2@TiO2 composite material photocatalyst samples were prepared. The difference was that the amount of TiO2 hollow spheres used in step (3) was 59.22 mg, 78.96 mg, 111.86 mg, 177.66 mg and 375.06 mg respectively. The mass ratios of TiO2 hollow spheres to CuGaS2 quantum dots in the obtained CuGaS2@TiO2 composite material photocatalysts were 0.75:0.25 for group S1, 0.8:0.2 for group S2, 0.85:0.15 for group S3, 0.9:0.1 for group S4 and 0.95:0.05 for group S5 respectively.

[0020] The crystal structures of the five groups of CuGaS2@TiO2 composite material photocatalysts prepared in Example 1 were tested by X-ray powder diffractometer (XRD). Figure 1 As shown. It can be seen that each group of samples contains two phase structures, namely, CuGaS2 quantum dots with chalcopyrite structure and TiO2 with anatase structure. As the CuGaS2 / TiO2 mass ratio increases, the (112) diffraction peak of the CuGaS2 quantum dots gradually increases. The peak intensity ratio of the (112) diffraction peak of the CuGaS2 quantum dots and the (101) diffraction peak of TiO2 is calculated. The ratio increases with the increase of the CuGaS2 / TiO2 mass ratio, indicating that the amount of quantum dots attached gradually increases.

[0021] The crystal structure of the CuGaS2@TiO2 composite material photocatalyst prepared in Example 1 was characterized by high resolution transmission electron microscopy (HRTEM). Figure 2 shown. Figure 2 (a) is the TEM image of TiO2 hollow spheres. Figure 2 (b)~(d) are TEM images of CuGaS2@TiO2 composite photocatalysts of S4 group. It can be seen that Figure 2 (c) and Figure 2 In (d), three different lattice fringes with widths of 0.352nm, 0.189nm, and 0.306nm were measured, corresponding to the (101) and (204) crystal planes of anatase TiO2 and the (112) crystal plane of chalcopyrite CuGaS2, respectively, indicating that a composite material of CuGaS2 quantum dots and TiO2 hollow spheres was successfully synthesized. Figure 2 The area shown in (b) is scanned by elements. Figure 2 (e) to (i) are the distribution of the five elements Cu, Ga, S, Ti, and O, respectively. It can be seen that they are evenly distributed. The above results show that this embodiment successfully uses the in-situ growth method to grow CuGaS2 quantum dots on the TiO2 surface.

[0022] X-ray photoelectron spectroscopy (XPS) was used to further analyze the oxidation state, chemical composition and valence band energy of the CuGaS2@TiO2 composite photocatalyst. Figure 3 shown. Figure 3 (a) is the full spectrum scan result, which shows the peaks corresponding to Cu 2p, Ga 3d, S2p, Ti 2p, O 1s and C 1s. Figure 3 (b)~(h) correspond to the narrow spectra of C 1s, Ti 2p, O 1s, Cu 2p, Ga 3d and S 2p and the Auger electron spectrum of Cu, respectively.

[0023] Since octadecene and oleylamine, which contain C elements, were used as solvents and surfactants in the synthesis process, a C 1s peak appeared. The C 1s peak at 284.8 eV was used as a reference point to calibrate the binding energy in the XPS test. The characteristic peak of Ti 2p showed the typical characteristics of two main peaks and satellite peaks of titanium compounds. The Ti 2p orbital was split into Ti 2p 3 / 2 and Ti 2p 1 / 2 The spin-orbit component has an energy difference of 5.74 eV, which is close to the typical energy difference of titanium compounds, △5.7 eV, proving that Ti in this complex exists in TiO2 in a positive tetravalent form. O 1s shows typical characteristic peaks and satellite peaks of metal oxides. -2 The Ga 3d orbital splits into Ga 3d 5 / 2 and Ga3d 3 / 2 The peak difference of the binding energy of the two orbitals is 0.46 eV, which is consistent with the presence of Ga(III) in the quantum dots. Due to the presence of oxygen atoms in TiO2, O 2s (23.5 eV) overlaps with the Ga 3d region. The S 2p orbital is split into two peaks and a satellite peak, corresponding to the S 2p 3 / 2 and S 2p 1 / 2 The spin-orbit component shows a typical 1.25 eV energy separation for sulfide materials and confirms that the S element in the quantum dot is S -2 There are no other characteristic peaks at higher binding energy, indicating that S mainly exists in the form of sulfide. The characteristic peaks of Cu2p show the typical characteristics of two main peaks and satellite peaks of copper compounds. 1 / 2 orbital is located at 931.63 eV, which is close to the Cu 2p3 / 2 The orbital binding energy difference is 19.83 eV, which excludes the existence of Cu(II). The Auger electron spectrum of Cu shows a kinetic energy of 917.16 eV, which is similar to the Cu 2p 1 / 2 The binding energies of the orbitals are added together to produce a total energy close to 1848.8 eV, which confirms that Cu exists in a positive monovalent form.

[0024] Example 2 Application of CuGaS2@TiO2 (CGS / TiO2) composite photocatalyst in degradation of organic pollutants 100 mL of 30 mg / L methyl orange (MO) solution was added to the reactor, and 10 mg of the 5 groups of photocatalysts and TiO2 hollow spheres prepared in Example 1 were added. The reactor was placed in a light-free environment, and magnetic stirring was used to keep the catalyst in a suspended or floating state. After 20 minutes, a sample was taken for determination and recorded as the initial value C0. Then, an 18 W UV-LED lamp was used for irradiation, and samples were taken for analysis at intervals of 10 minutes during the illumination process and recorded as C t After centrifugation, the supernatant was measured by spectrophotometer MO =455nm to measure the absorbance, and use the formula: ƞ=[(1-C t / C0)]*100% to calculate the degradation rate, where C0 is the absorbance of the solution when adsorption equilibrium is reached, C t The absorbance is measured by sampling at regular intervals. Figure 4 shown.

[0025] Figure 4 (a) is the degradation of methyl orange by TiO2 hollow spheres. Figure 4 (b) shows the degradation of methyl orange by different groups of photocatalysts. Figure 4 (c) is the degradation of methyl orange by the photocatalyst of group S4. After 30 minutes of light irradiation, the degradation rate of methyl orange by each group of photocatalysts is calculated as follows: Figure 4 As shown in (e), they are 84.93% for TiO2 hollow spheres, 92.83% for S1 group, 93.17% for S2 group, 94.76% for S3 group, 95.72% for S4 group, and 91.92% for S5 group. The degradation rate of S4 group is the highest when the mass fraction of CuGaS2 quantum dots is 10%. With the increase of the mass fraction of quantum dots, the degradation ability slowly decreases. This may be due to the fact that too many quantum dots cover the surface of TiO2 hollow spheres, affecting the light absorption rate, thus weakening the degradation ability. The addition amount of quantum dots is an important factor affecting the degradation ability of CuGaS2@TiO2 composite material photocatalyst.

[0026] At the same time, the degradation of methyl orange by CuGaS2 quantum dots, TiO2 hollow spheres and CuGaS2@TiO2 in S4 group was compared. Figure 4 (f) and Figure 4 (g) is shown. Figure 4 (f) It can be seen that when CuGaS2@TiO2 is used to degrade methyl orange, the concentration of methyl orange decreases rapidly, while the degradation rate of methyl orange by TiO2 hollow spheres is relatively slow. Figure 4 (g) is the relationship between -ln (C / C0) and illumination time (t) of the degradation of methyl orange by the three agents, all of which show a linear relationship, which is in line with the law of reaction kinetics. The pseudo-first-order rate constants of the degradation of methyl orange by the three agents are calculated to be 0.0045 min -1 , 0.0643 min -1 and 0.1031 min -1 The photocatalytic degradation rate of CuGaS2@TiO2 composite material is 22.91 times higher than that of CuGaS2QDs and 1.6 times higher than that of TiO2 hollow spherical shells.

[0027] After centrifuging the used photocatalyst, it was washed twice alternately with deionized water and anhydrous ethanol, dried and reused to carry out a recycling experiment. Figure 4 (h) is the cyclic degradation experimental result of CuGaS2@TiO2 on methyl orange in the S4 group. It can be seen that its degradation ability is relatively stable. After four cycles of use, the degradation rate remains above 94% after 30 minutes of illumination. The results show that the CuGaS2QDs dots are successfully grown on the surface of TiO2 hollow spheres through the in-situ growth method, and the two directly form a heterostructure.

[0028] To explore the photogenerated holes (h + )、Photogenerated electrons(e - ), hydroxyl radicals (·OH) and superoxide radicals (·O2 - ) in the process of photocatalytic degradation. Before the degradation reaction of methyl orange, the hole sacrificial agent (1 mL methanol, MT), the electron sacrificial agent (1 mL 30 mg / L manganese acetate, MA), the hydroxyl radical sacrificial agent (1 mL isopropanol, IPA), and the superoxide radical sacrificial agent (nitrogen protection, N2) were loaded into the reaction system. Figure 4 (d) is the UV-VIS absorption spectrum of methyl orange after adding different sacrificial agents for 30 minutes. Figure 4 (i) The addition of hole sacrificial agent and superoxide radical sacrificial agent has a greater effect on the degradation rate of methyl orange, and the degradation rate is reduced to 48.61% and 32.93%, while the hydroxyl radical sacrificial agent and electron sacrificial agent have relatively small effects, and the degradation rate is reduced to 70.84% ​​and 85.77%, indicating that in the process of photocatalytic degradation of methyl orange by CuGaS2@TiO2 composite, h + and O2 - Play a leading role.

[0029] The EVB standard hydrogen electrode (NHE) potentials of CuGaS2 and TiO2 are +1.58eV and +3.1eV, respectively, and the ECB are -1.25eV and -0.1eV, respectively. Under ultraviolet light irradiation, both CuGaS2QDs and TiO2 hollow spheres will be excited, electrons will jump from the valence band to the upper band, and holes will remain in the valence band. The electron and hole transfer between CuGaS2 quantum dots and TiO2 hollow spheres may follow the type II heterojunction and direct Z-type heterojunction. If the type II heterojunction is followed, then e - The conduction band of CuGaS2QDs is transferred to the conduction band of TiO2 hollow spheres. + The valence band of the TiO2 hollow sphere will be transferred to the valence band of CuGaS2 QDs, but since the ECB of TiO2 is -0.1 eV higher than that of O2 - The standard redox potential of (-0.33 eV vs. NHE) is corrected, and there is insufficient reaction kinetics to generate the e in the TiO2 conduction band. - Will not react with O2 to produce O2 - This contradicts the conclusion of the quenching experiment, so the e between CuGaS2 quantum dots and TiO2 hollow spheres - 、h + The transfer does not conform to a type II heterojunction.

[0030] If we follow the direct Z-type heterojunction, then the e on the TiO2 conduction band - can be transferred to the valence band of CuGaS2, thereby effectively reducing the recombination of electron-hole pairs and improving the photocatalytic activity. The ECB of CuGaS2 is higher than that of O2 - The standard redox potential is more negative, and electrons in the CuGaS2 conduction band can react with O2 to produce O2 - , the EVB ratio of TiO2 is ·OH / H2O (+2.27eVvs. NHE) and ·OH / OH - (+1.99 eV vs. NHE) standard redox potential correction, h + Can be with H2O or OH - The reaction generates ·OH, which is consistent with the conclusion of the quenching experiment. Therefore, the e between CuGaS2 quantum dots and TiO2 hollow spheres - 、h + The transfer follows a direct Z-type heterojunction. + and ·OH, ·O2 obtained by the reaction - , H2O2 oxidizes methyl orange and decomposes it into intermediate substances, CO2, H2O and other products.

[0031] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a CuGaS2@TiO2 composite material photocatalyst, characterized in that: The following steps are involved: After mixing copper source, gallium source, octadecene and oleylamine, add TiO2 hollow spheres and mix evenly under protective gas; add sulfur precursor solution, heat to 180-260℃, react for 25-30min; quench and purify; Among them, the dosage ratio of the copper source, gallium source, octadecene, oleylamine, sulfur precursor solution and TiO2 hollow spheres is 0.1mmol:0.1mmol:10mL:3mL:1mL:0.7~4.7mmol, the sulfur precursor solution is an oleylamine solution of sulfur powder, and the dosage ratio of sulfur powder to oleylamine is 1mmol:1mL.

2. The method for preparing the CuGaS2@TiO2 composite material photocatalyst according to claim 1, characterized in that: The preparation method of the TiO2 hollow spheres is as follows: titanium tetrachloride and acetone are added to anhydrous ethanol, and a hydrothermal reaction is carried out at 220° C. in a high-pressure reactor for 12 hours. After cooling, the product is washed to neutrality, dried, and calcined at 650° C. for 150 minutes to obtain the product.

3. The method for preparing the CuGaS2@TiO2 composite material photocatalyst according to claim 2, characterized in that: The usage ratio of titanium tetrachloride, acetone and anhydrous ethanol is 1 mL:24 mL:96 mL.

4. The method for preparing the CuGaS2@TiO2 composite material photocatalyst according to claim 1, characterized in that: The copper source is cuprous chloride, and the gallium source is gallium chloride.

5. The method for preparing the CuGaS2@TiO2 composite material photocatalyst according to claim 1, characterized in that: The quenching method is to rapidly cool in a 25° C. cold water bath.

6. The method for preparing the CuGaS2@TiO2 composite material photocatalyst according to claim 1, characterized in that: The purification method comprises washing the precipitate with anhydrous ethanol after centrifugation to obtain the CuGaS2@TiO2 composite material photocatalyst.

7. A CuGaS2@TiO2 composite material photocatalyst, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 6.

8. The CuGaS2@TiO2 composite material photocatalyst according to claim 7, characterized in that: The CuGaS2@TiO2 composite material photocatalyst is a TiO2 hollow sphere surface loaded with CuGaS2 quantum dots to form a direct Z-type heterostructure, wherein the mass fraction of the CuGaS2 quantum dots is 5-25%.

9. Use of the CuGaS2@TiO2 composite material photocatalyst according to claim 7 or 8 in degrading organic pollutants.

10. The use of the CuGaS2@TiO2 composite material photocatalyst in degrading organic pollutants according to claim 9, characterized in that: The organic pollutant is methyl orange.

Citation Information

Cited By

  • Sulfur gallium zinc copper / titanium dioxide composite photocatalyst as well as preparation method and application thereof

    CN120618490A

  • A sulfogallium zinc copper / titanium dioxide composite photocatalyst and a preparation method and application thereof

    CN120618490B